Higher order mode dielectric resonator antenna excited using microstrip line - Irfan Ali; Mohd Haizal Jamaluddin; Abinash Gaya (Bulletin of Electrical Engineering and Informatics, 2020)
In this paper, the square-shaped dielectric resonator antenna (DRA) operating on higher order (????????????13) mode for the fifth generation (5G) communication applications is presented. The proposed DR antenna is excited by using a microstrip feed line and designed at the operating frequency of 28 GHz. The Rogers RT/Duroid 5880 material having a thickness of 0.254mm and a dielectric constant of 2.2 is used for the substrate. The commercial CST microwave studio (CST MWS) is used for the optimization and simulation of the antenna design. The reflection coefficient, antenna gain, radiation efficiency, VSWR and radiation pattern are studied. A -10dB bandwidth of 4.6% (1.3 GHz) for VSWR less than 2 with a gain of 5 dBi and radiation efficiency of 89%. The proposed antenna design is suitable for future 5G wireless communication applications.